INVENTARISASI JAMUR PENYEBAB PENYAKIT PADA TANAMAN KRISAN (Chrysanthenum morifolium) DI KECAMATAN BERASTAGI, KABUPATEN KARO, SUMATERA UTARA - Lisnawita Lisnawita Daniel Erikson Hutabarat1*, Lisnawita2, Lahmuddin Lubis2; Lahmuddin Lubis2; Daniel Erikson Hutabarat (Jurnal Agroekoteknologi, 2014)
Researech on tittle the inventarization fungus which is caused diseases on Chrysanthemummorifolium in Sub-district Berastagi, Regency Karo, North Sumatera. This research was intents toknow and to inventary fungus that caused Chrysanthemum morifolium disesases in field and ingreen house in Sub-district Berastagi, Regency Karo, North Sumatera. This research carried out inLaboratory of Plant Pathology Faculty of Agriculture, University of North Sumatera . The Resultsof this research showed that fungus caused Chrysanthemum morifolium diseases were cultivated infield are Puccinia horiana, Septoria sp., Fusarium sp. on flower, and Fusarium sp. on the stem,whereas Chrysanthemum morifolium were cultivated in green house are Puccinia horiana andSeptoria sp..Keywords : inventarization, fungus, Chrysanthemum morifolium